Stock Screening Process for Shariah Compliance: Global Practices - Md Habibur, Rahman (2018)
Stock screening process for Sharīʻah compliance refers to a certain process to select the stocks and shares accordingly and to make them enlisted as Sharīʻah compliant stocks. Using discussion and analytical method this article comparatively discusses several methodologies to screen for Sharīʻah complaint shares that have been utilized worldwide. Usually two aspects are important in the screening process, business transactions screening and financial transactions screening. In the screening process a specific threshold of Sharīʻah non-compliant elements, such as illegal income and profit, is overlooked considering the principles of collective needs, public wellbeing, common plight and so forth. Generally, a percentage of illegal wealth present is tolerated - 5% in business screening and 33% in the financial screening. However, profit arising from these illegal elements neither shall be distributed among the shareholders nor shall it be used in any beneficial scheme of the company such as tax deduction, zakat exemption and the like. The profit amount shall be disposed for charitable purposes instead.